Modern Jewish baker : challah, babka, bagels & more - Sarna, Shannon (The Countryman Press, a division of W. W. Norton & Company, Inc., 2017)
Jewish baked goods have brought families together around the table for centuries. In Modern Jewish Baker, Sarna pays homage to those traditions while reinvigorating them with modern flavors and new ideas. One kosher dough at a time, she offers the basics for challah, babka, bagels, hamantaschen, rugelach, pita, and matzah. Never one to shy away from innovation, Sarna sends her readers off on a bake-your-own adventure with twists on these classics.